Pernicious pests and public perceptions: Wilding conifers in Aotearoa New Zealand. (September 2020) - Edwards, Peter; Stahlmann-Brown, Philip; Thomas, Simon
Highlights: Wildings and their negative aspects are increasingly recognised in New Zealand Many landowners and others volunteer to control wildings but need more support Mechanical means of control have highest levels of approval over spraying All aspects of wilding control require careful consideration for public acceptance Abstract: With significant favourable natural resources, New Zealand has excellent growing conditions for certain exotic conifer species. Although these species have been used for erosion control, and commercial and shelter/amenity plantings for many decades, they do have a high propensity to spread into undesirable locations around the country through natural means. These wilding conifers have become pests. Over the years, these pests have been controlled by landowners, government and community members using various methods, including mechanical and chemical means. Further, new ways of control have also been proposed, including the use of fire, genetics and other technologies. In this paper we examine survey and follow-up focus group data to understand public acceptance of these control methods. Overall, mechanical and selective chemical means were most accepted, while widespread chemical spraying and novel or alternative methods were less acceptable. The survey results and focus group discussions highlight the local, contextual nature of the challenges and opportunities.